PERLINDUNGAN HUKUM TERHADAP PEKERJA PEREMPUAN MENURUT KETENTUAN UNDANG-UNDANG KETENAGAKERJAAN - Rosifany, Ony (Universitas 17 Agustus 1945 Samarinda, 2019)
Protection of women workers can be done, both by making demands and by increasing the recognition of human rights, physical and technical as well as social and economic protection through norms applicable in the work environment.Workforce protection is to guarantee a harmonious working relationship system without pressure from the strong to the weak. For this the employer is obliged to implement the labor protection provisions in accordance with the applicable laws and regulations.Law enforcement is an important part of the legal system, this is done as an effort to develop systematically and continuously. Implementation of legal sanctions, both administrative and criminal as a result of violation of a provision in the legislation.